Enhanced point of care ultrasound skills after additional instruction from simulated patients (Canadian Medical Education Journal, 2022)
Background: Point of Care Ultrasound (POCUS) training in Canadian undergraduate medical programs is steadily increasing. To date, the simulated patients (SPs) in our program have only provided feedback on comfort and professionalism. Involving the POCUS SPs as teachers (SP-teachers) of POCUS skills provides an additional opportunity for instruction. In this pilot study, we explored the impact of SP-teachers instructing medical trainees while they learned POCUS. Outcomes of interest included the level of proficiency achieved after the session and trainee satisfaction with the learning experience. Methods: Second year medical students were randomized into a conventional or SP-teacher learning experience. Both groups received the same video tutorial, instructor guidance, and basic SP feedback (comfort and professionalism). The SP-teaching group received additional instruction (landmarks, transducer technique, and troubleshooting) from the SP-teachers when session instructors were assisting others. Students evaluated the session and were subsequently assessed through direct observation.Results: Students that received SP-teaching scored significantly higher in both image acquisition (p = 0.029, d = 1.26) and overall entrustment (p = 0.002, d =1.75). Both groups rated their sessions highly. Conclusions: Students that received SP-teaching were observed to better acquire images and achieved higher entrustment scores. In this pilot study, SP-teachers had a positive effect on acquisition of POCUS skills.